Peri-urban dairy Development in sub-Saharan Africa: analysis of constraints and opportunities - Shapiro, Barry I.; Ehui, Simeon K.; Fitzhugh, H.A. (World Association for Animal Production, 1995)
This paper addresses the constraints and opportunities to dairy Development in sub-Saharan Africa, as well as the role that international research can play to promote this process. It first discusses present and projected future demand and supply conditions, and on-going changes in international trade policy, as well as domestic policies. Then, the constraints faced and the opportunities these afford are highlighted. next, the approach to research used by the International Livestock Research Institute (ILRI) that involves a conceptual framework is described, including the on-going work with its collaborators in National Agricultural Research Systems (NARS) through one of its research networks. Then, based on results so far of ILRI's research on peri-urban dairying, the intensified nature of the Development taking place in the various types of production systems is highlighted, as well as the role for support services. Lastly, future ocntributions that international livestock research can make in promoting dairying are discussed.